Ski orientation determination from GPS/IMU derived trajectory - Waegli, A.; Meyer, F.; Skaloud, J.; Borrani, F. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: In alpine skiing, the determination of accurate orientations of a ski is the prerequisite for analyzing measurements of force plates fixed under the boots. Indeed, in order to decompose the forces encountered in a turn and to isolate the gravitational force, the orientation of the ski is required. Nowadays, the ski's orientation can be obtained from multi-camera Systems with a precision of five degrees for an object orientation (Richards 1999). However, this method requires an important infrastructure and is not adapted for everyday use and training purposes. The method described below proposes a new approach that is more accurate, faster, and easier to setup and is insensitive to the weather conditions.